Neurotensin Attenuates Nociception by Facilitating Inhibitory Synaptic Transmission in the Mouse Spinal Cord - Zhang, Ming-Ming; Feng, Yu-Peng; Qiu, Xin-Tong; Chen, Tao; Bai, Yang; Feng, Jia-Ming; Wang, Jun-Da; Chen, Yan; Zhang, Ming-Zhe; Duan, Hao-Kai; Zhao, Mingwei; Teng, Yi-Hui; et al. (Frontiers in Neural Circuits, 2021)
Neurotensin (NT) is an endogenous tridecapeptide in the central nervous system. NT-containing neurons and NT receptors are widely distributed in the spinal dorsal horn (SDH), indicating their possible modulatory roles in nociception processing. However, the exact distribution and function of NT, as well as NT receptors (NTRs) expression in the SDH, have not been well documented. Among the four NTR subtypes, NTR2 is predominantly involved in central analgesia according to previous reports. However, the expression and function of NTR2 in the SDH has not yet been directly elucidated. In specificSpecifically, it remains unclear how the NT-NTR2 interactions contribute to NT-mediated analgesia. In the present study, by using immunofluorescent histochemical staining and immunohistochemical staining with in situ hybridization histochemical staining, we found that dense NT- immunoreactivity (NT-ir) and moderate NTR2-ir neuronal cell bodies and fibers were localized throughout the superficial laminae (laminae I-II) of the SDH at the light microscopic level. In addition, γ-aminobutyric acid (GABA) and NTR2 mRNA were co-localized in some neuronal cell bodies, predominantly in lamina II. Using confocal and electron microscopy, we also observed that NT-ir terminals made both close contacts and asymmetrical synapses with the local GABA-ir neurons. Second, the electrophysiological recordings showed that NT facilitated inhibitory synaptic transmission but not glutamatergic excitatory synaptic transmission. Inactivation of NTR2 abolished the NT actions on both GABAergic and glycinergic synaptic release. Moreover, a behavioral study revealed that intrathecal injection of NT attenuated thermal pain, mechanical pain, and formalin induced acute inflammatory pain primarily by activating NTR2. Taken together, the present results provide direct evidence that NT-containing terminals and fibers, as well as NTR2-expression expressing neurons are widely distributed in the spinal dorsal horn, GABA-containing neurons express NTR2 mainly in lamina II, GABA coexists with NTR2 mainly in lamina II, and NT may directly increase the activity of local inhibitory neurons through NTR2 and induce the analgesic effects.